2021
DOI: 10.3389/fpls.2021.634960
|View full text |Cite
|
Sign up to set email alerts
|

Life on the Rocks: First Insights Into the Microbiota of the Threatened Aquatic Rheophyte Hanseniella heterophylla

Abstract: Little is known about microbial communities of aquatic plants despite their crucial ecosystem function in aquatic ecosystems. Here, we analyzed the microbiota of an aquatic rheophyte, Hanseniella heterophylla, growing at three areas differing in their degree of anthropogenic disturbance in Thailand employing a metabarcoding approach. Our results show that diverse taxonomic and functional groups of microbes colonize H. heterophylla. Proteobacteria, Actinobacteria, Dothideomycetes, and Sordariomycetes form the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 103 publications
2
2
0
Order By: Relevance
“…Therefore, DNA was extracted from the whole rock surface. A similar result was observed by Purahong et al [43] , who showed that cyanobacteria diversity was negatively affected in highly disturbed areas. Chloroflexi, instead, are known to be involved in the formation of matrixes that allow the aggregation of external material and it is more likely that they form on a more stable substrate [44] .…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, DNA was extracted from the whole rock surface. A similar result was observed by Purahong et al [43] , who showed that cyanobacteria diversity was negatively affected in highly disturbed areas. Chloroflexi, instead, are known to be involved in the formation of matrixes that allow the aggregation of external material and it is more likely that they form on a more stable substrate [44] .…”
Section: Discussionsupporting
confidence: 89%
“…The average value of percent functional assignment of FUNGuild is 43% (ranging from 38-46%). These values are consistent with the percentage points of functional assignment of FUNGuild reported before in many publications [39,46,47]. Nevertheless, it is known that the percentage points of functional assignments of taxonomically dependent functional annotation tool highly depends on the quality and quantity of the database backbone of each sequence data, taxonomic identification and functional description [48].…”
Section: Performance Of Ecological Function Assignments Of Funguild A...supporting
confidence: 89%
“…R was used to examine microbial alpha diversity (Veen Diagram package). Utilizing Mothur [ 40 ] 1.30.2, OTU Venn analyses of several biomes were conducted. The beta diversity distances were calculated using QIIME 1.9.1, and pairwise categorical distance matrices between bacterial communities were analyzed using the Bray–Curtis method.…”
Section: Methodsmentioning
confidence: 99%